2019
DOI: 10.1080/1612197x.2019.1593215
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of teammate moral behaviour: Linking team moral norms with cohesion and collective efficacy

Abstract: The aim of the Leeds Beckett Repository is to provide open access to our research, as required by funder policies and permitted by publishers and copyright law. The Leeds Beckett repository holds a wide range of publications, each of which has been checked for copyright and the relevant embargo period has been applied by the Research Services team. We operate on a standard take-down policy. If you are the author or publisher of an output and you would like it removed from the repository, please contact us and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…In fact, the observance of behavioral factors towards others (fans, athletes, coaches, athletes' families, and so on), by the referees, leads to the growth of ethics in the sports environment. The results of this research in this section are consistent with the results ofHajipour et al (2019) andPizzi (2019). Therefore, the Iran's sports referees are recommended to use appropriate behavioral factors when dealing with people in sports environments.…”
supporting
confidence: 91%
“…In fact, the observance of behavioral factors towards others (fans, athletes, coaches, athletes' families, and so on), by the referees, leads to the growth of ethics in the sports environment. The results of this research in this section are consistent with the results ofHajipour et al (2019) andPizzi (2019). Therefore, the Iran's sports referees are recommended to use appropriate behavioral factors when dealing with people in sports environments.…”
supporting
confidence: 91%
“…Despite the initial difficulties of the coach in the intervention to offer opportunities to athletes to be more active in their learning process collaborating with each other and allowing them to teach an activity or skill to the team, the impact on prosocial behavior has been high. This finding led us to affirm that TPSR model intervention in competitive sports contexts could involve improvements in youth prosocial behavior if the coach use specific strategies related to Level III (Self-direction) and Level IV (Leadership and caring) and other examples of strategies as constructive feedback, supporting, congratulating, and encouraging one's teammates that contribute to experience a more pleasant sport experience and lead athletes to try harder and perform better (Kavussanu and Stanger, 2017;Pizzi and Stanger, 2019). As expected in the initial hypothesis, the athletes who participated in the experimental group obtained significant improvements in social responsibility over those in the control group after participating in the program.…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, the negative experience of antisocial teammate behaviour could diminish athletes' ability to cope with the demands of their sport (Kavussanu, 2012;). Antisocial teammate behaviour negatively predicted task and social cohesion (Pizzi & Stanger, 2019) and positively predicted burnout (Al-Yaaribi & Kavussanu, 2017) in team-sport athletes. The relationships with cohesion and burnout were both direct and indirect via negative affect, underlining the importance of affect as a mechanism through which antisocial teammate behaviour may influence cohesion and burnout.…”
Section: Antisocial Teammate Behaviourmentioning
confidence: 96%
“…Task cohesion refers to the degree to which team members are united in working together toward achieving team goals, whereas social cohesion reflects the degree to which team members like each other, get along, and consider one another to be friends (Eys, Loughead, Bray, & Carron, 2009). In two studies of team sport athletes, prosocial teammate behaviour positively predicted both task and social cohesion (Al-Yaaribi & Kavussanu, 2017;Pizzi & Stanger, 2019); in one of these studies, the relationship with task cohesion was partially mediated by positive affect (Al-Yaaribi & Kavussanu, 2017). In other research, participants reported that their social identity was strengthened when they perceived their teammates engaging in prosocial behaviours , while adolescent hockey players' social identity was stronger on days in which they experienced more prosocial behaviours from their teammates .…”
Section: Prosocial Teammate Behaviourmentioning
confidence: 97%